Effects of feeding varied levels of balanced protein on growth performance and carcass composition of growing and finishing pigs - Shelton, N.W.; Htoo, J.K.; Redshaw, M.; Goodband, Robert D.; Tokach, Michael D.; Nelssen, Jim L.; DeRouchey, Joel M.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A total of 1,003 barrows and gilts (PIC 337 × 1050, initially 113.5 lb) were used in an 88-d study to determine effects of various levels of balanced amino acid density on growth performance and carcass characteristics. Balanced amino acid refers to balancing the dietary amino acids according to the ideal protein ratio, at least for the first 4 limiting amino acids; the other amino acids may be at or higher than required levels. In this study, this balance was accomplished by using supplemental amino acids and formulating to meet the first 4 limiting amino acids: lysine, threonine, methionine, and tryptophan. Three experimental diets were tested using 6 replicate gilt and 7 replicate barrow pens per treatment. These diets were tested over 2 different phases, a grower phase (d 0 to 28) and a finishing phase (d 28 to 88). Dietary treatments included a diet that met the NRC (1998)5 requirements, a diet that met Evonik Degussa (Hanau, Germany) requirements, and a diet that was formulated to be 10% greater than Evonik Degussa recommendations. No gender × dietary treatment interactions were observed (P > 0.30) for any of the growth or carcass characteristics. During the growing phase, ADG and F/G improved (linear; P < 0.03) as amino acid density increased in the diet. Also, gilts had decreased (P < 0.001) ADFI and improved (P < 0.001) F/G from d 0 to 28 compared with barrows. During the finishing phase, no differences were observed (P > 0.62) in ADG, ADFI, or F/G from increasing dietary lysine or balanced protein levels. Gilts had decreased (P < 0.001) ADG and ADFI compared with barrows. Over the entire 88-d trial, F/G improved (linear; P < 0.04) and a trend was detected for improved (linear; P < 0.06) ADG as dietary amino acid density increased. No dietary treatment differences were observed (P > 0.28) for carcass yield, backfat depth, loin depth, percentage lean, live value, or calculated income over feed cost. In this experiment, increasing the amino acid density (dietary lysine level) over the NRC (1998) requirement offered improvements in the grower phase but not the finishing phase.
Keywords: Amino acid; Lysine; Swine